2019
DOI: 10.1101/534099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear in dreams and in wakefulness: evidence for day/night affective homeostasis

Abstract: Recent neuroscientific theories have proposed that emotions experienced in dreams contribute to the resolution of emotional distress and preparation for future affective reactions. We addressed one emerging prediction, namely that experiencing fear in dreams is associated with more adapted responses to threatening signals during wakefulness. Using a stepwise approach across two studies, we identified brain regions activated when experiencing fear in dreams and showed that frightening dreams modulated the respo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 84 publications
6
27
0
1
Order By: Relevance
“…The main goal of this study was to determine whether there exist distinct transient brain states of the sleeping brain that may play a critical role in experiencing and remembering dreams during NREM sleep. A couple of previous studies suggested different brain regions and frequency modulations to be associated with the conscious experience during NREM sleep 13 , 16 , 17 , 26 28 . By using the EEG microstate approach, which identifies brain states by the spatial properties, rather than the spectral content of the EEG, we were able to identify and precisely time two microstates that dominate during sleep as compared to awake, and found that these two states dissociated the EEG during dreaming and no dreaming: microstate 3 was more present when participants reported their dreams, while microstate 4 dominated when no dreams were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of this study was to determine whether there exist distinct transient brain states of the sleeping brain that may play a critical role in experiencing and remembering dreams during NREM sleep. A couple of previous studies suggested different brain regions and frequency modulations to be associated with the conscious experience during NREM sleep 13 , 16 , 17 , 26 28 . By using the EEG microstate approach, which identifies brain states by the spatial properties, rather than the spectral content of the EEG, we were able to identify and precisely time two microstates that dominate during sleep as compared to awake, and found that these two states dissociated the EEG during dreaming and no dreaming: microstate 3 was more present when participants reported their dreams, while microstate 4 dominated when no dreams were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Another intriguing, complementary, hypothesis that comes to mind when looking at the general pattern of data is the existence of some sort of “day/night affective homeostasis” (an idea already suggested by [ 75 ]), with the dreaming experience of negative emotions balancing the prevalent expression of positive affect during wake time.…”
Section: Discussionmentioning
confidence: 99%
“…According to the idea that DE play a role in the emotional processing, more recently awake fMRI measures revealed that subjects experiencing frequent fear during DE have a higher activation of mPFC and reduced activation in the insula, amygdala and midcingulate cortex when faced with aversive stimuli (Sterpenich et al, 2019 ). The results are consistent with the view that mPFC should exert an inhibitory control on fear expression by reducing amygdala activity (Phelps et al, 2004 ).…”
Section: Neural Bases Of Dreaming and Emotional Processingmentioning
confidence: 99%